Factors creating favorable conditions for activating innovative entrepreneurship and startups in post-war Ukraine - Oksana Khymych; Enno Masurel (Problems and Perspectives in Management)
As global conflicts and hostilities become more prevalent, it is essential to investigate the conditions necessary for the operation and growth of innovative enterprises considering post-war recovery. The paper aims to determine crucial favorable conditions for activating innovative entrepreneurship and startups in the post-war period in Ukraine. The analysis is based on inductive, qualitative data from 24 interviews with the respondents from Ukraine and the Netherlands (eight scientists, ten startup founders and entrepreneurs, two government officials, and four entrepreneurs) to identify a range of favorable factors by utilizing qualitative analysis. The paper used individual, in-depth, semi-structured interviews. The study identified eight constraining aggregate themes (the consequences of war, policy and regulatory system, market and investment, the ecosystem, passive universities, education and skills, internationalization, and culture) and three enabling aggregate themes (the consequences of war, active universities, and the ecosystem) through the grouping of factors from the second-order code. The most significant constraining factor from aggregate themes “the consequences of war” is brain drain (40.63%). Among the eight constraining aggregate themes, 32.55% identified the policy and regulatory system as the main obstacle due to the absence of an effective strategy, ineffective legislation, passive municipalities, and bureaucracy. Moreover, the lack of funds is a critical issue in addressing the consequences of the war, financing startup projects, and creating favorable conditions. The results emphasize constraining and enabling conditions for activating innovative entrepreneurship and startups. Such results are helpful for policymakers to improve the conditions for startup development by overcoming the immediate identified obstacles. AcknowledgmentThe publication was prepared in the framework of the MSCA4Ukraine postdoctoral fellowship (Oksana Khymych Ref.№ UKR 1233171), which is funded by the European Union that provides support and funding for the Ukrainian researchers displaced by the war, while the Consortium (a consortium comprised of Scholars at Risk Europe hosted at Maynooth University, Ireland (project coordinator), the German Alexander von Humboldt Foundation (AvH) and the European University Association (EUA)) is a collaborative network of institutions managing and implementing this initiative. The views and opinions expressed in this report are solely those of the authors and do not reflect the views of the European Union or the MSCA4Ukraine Consortium. Neither the European Union, the MSCA4Ukraine Consortium, nor any individual member institutions of the Consortium can be held responsible for these views and opinions. We would like to express our sincere gratitude to the colleagues at Vrije Universiteit Amsterdam for their invaluable support in conducting the research and for fostering an environment conducive to academic excellence and innovation.